The fine art of small talk : how to start a conversation, keep it going, build networking skills, and leave a positive impression - Fine, Debra (New York : Hyperion, 2005)
Techniques to starting a conversation and building networking skills with tips on avoiding silences, leaving a positive impression, and being self-assured.
What's the big deal about small talk? -- Get over your mom's good intentions -- Take the plunge: start a conversation! -- Keep the conversation going! -- Let's give 'em something to talk about -- Hearing aids and listening devices -- Prevent pregnant pauses with preparation -- Conversational clout -- Crimes and misdemeanors -- The graceful exit -- The conversational ball is in your court! -- Make the most of networking events! -- Surviving the singles scene -- Feel-good factor -- Holiday party savvy -- Carpe diem.
Keywords: Conversation; Oral communication; Conversation; Conversation; Oral communication; Smalltalk; Konversation; 0